The compound sentence of attributive type in the scientific style (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
Have been analyzed compound sentences of attributive type in terms of their semantic and syntactic function in the in scientific and educational texts of transport (railway) direction.
Keywords: compound sentence of definite type; conjunction; conjunction word; reference word